Modelling and 3D Visualisation of Landscape Changes in the Rosia Montana Basin - Gábor Barton; Katalin Bódis; Róbert Géczi (European Regional Science Association (ERSA), 2005)
The town of Rosia Montana is located above one of the largest gold and other precious metal deposits in Europe. Gold and silver have been mined for centuries here, even as early as pre-roman times. Since then, and predominantly in the 20th century the landscape has undergone significant changes. Until the dawn of open pit mining the ores were extracted using shafts and tunnels, leaving little if any traces on the surface. Large-scale open cast mining began in the first half of the 20th century and two large pits were excavated in the immediate vicinity of the little town. After a few decades these were closed down, relocating the mining activities into a neighbouring valley. Presently the Rosia Montana Gold Corporation is planning on reopening the gold deposits in the area by starting the largest open cast mine site in Europe. The project aroused much controversy and international protests regarding its consequences on the population and the environment. The current study aims to model the landscape in the past in some selected time periods. In addition, a significant section will attempt to predict and visualise the future landscape after the full development of the project. Also, a time series animation is included to demonstrate the changes in time.
Keywords: 330